Psychosocial adjustment and parental stress in Duchenne Muscular Dystrophy. (November 2019) - Gocheva, Vanya; Schmidt, Simone; Orsini, Anna-Lena; Hafner, Patricia; Schaedelin, Sabine; Weber, Peter; Fischer, Dirk
Abstract: Objective: This cross-sectional study aimed to assess psychosocial adjustment of children with Duchenne Muscular Dystrophy (DMD) and to explore its possible association to parental stress. Methods: 34 children with DMD, 9–14.1 years of age, and their parents were included in the study. Caregivers completed the Child Behaviour Checklist (CBCL), the Psychosocial Adjustment and Role Skills Scale III (PARS-III) and the Parenting Stress Index–Short Form (PSI-SF). Patients older than 11 years completed the Youth Self Report (YSR). Regression analyses including parental stress, socio-demographic and disorder-related factors were performed to determine how these aspects influence the psychosocial adjustment in children with DMD. Results: Depending on the measure, 15%–47% of children with DMD were found to be psychosocially "at risk" for emotional and behavioural problems. Age showed no association with psychosocial adjustment. Half of the caregivers experienced very high parenting stress. Moreover, the two aspects parent-child dysfunctional interaction and difficult child scores were associated to psychosocial adjustment. Regression analyses showed that both parental stress and participation in a DMD support group are related to the psychosocial adjustment. Conclusions: The PARS-III represents a more suitable instrument assessing psychosocial adjustment in DMD, since compared to the CBCL it excludes physiological symptoms regarding chronic diseases. Decreased parents' stress levels and participation in a DMD support group positively contributed to good psychosocial adjustment. A family-centered approach is crucial for interventions in order to improve the psychosocial adjustment of these children and their families even while living with the significant burdens associated with DMD. Highlights: 15%–47% of children with DMD exhibit psychosocial adjustment problems. Almost half of caregivers of children with DMD report very high levels of stress. Decreased parents' stress positively contribute to good psychosocial adjustment. Support group participation positively contribute to good psychosocial adjustment.